Proportion optimization of honey pineapple juice on the custard organoleptic and chemical properties - Siti Susanti; Lutviana Tiaswuni; Ahmad Ni’matullah Al-Baarri; Yasmin Aulia Rachma (International Journal of Advances in Applied Sciences, 2024)
Custard is categorized as a dairy product that has a sweet taste, soft, and thick texture. The addition of honey pineapple to custard making is an innovation to improve the organoleptic and chemical characteristics of custard. The purpose of this study is to know the effect of adding honey pineapple juice on the organoleptic and chemical properties of pineapple custard. The experimental design used 5 treatments and 4 replications. The study began with the process of making custard products according to the addition of honey pineapple juice treatments there are P0 (control), P1 (20%), P2 (40%), P3 (60%), and P4 (80%). The test method is done by organoleptic and proximate analysis tests. The results of the organoleptic test showed that the addition of honey pineapple juice affects the color, taste, aroma, and overall preference of pineapple custard. Proximate analysis showed that the addition of pineapple juice honey affected the water content, ash content, fat content, and carbohydrate content of pineapple custard. This study concludes that the difference in the proportion of pineapple honey affects the organoleptic and chemical characteristics of pineapple custard.